thực hiện phép tính:
a)2.(50+35):(-20+3)
b)(-4).17+(-4).83-(-50)
c)10.(-8)+(-10).(-8)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: Ta có: \(A=\sqrt{8}-2\sqrt{18}+3\sqrt{50}\)
\(=2\sqrt{2}-6\sqrt{2}+15\sqrt{2}\)
\(=11\sqrt{2}\)
b: Ta có: \(B=\sqrt{125}-10\sqrt{\dfrac{1}{20}}+\dfrac{5-\sqrt{5}}{\sqrt{5}}\)
\(=5\sqrt{5}-\sqrt{5}+\sqrt{5}-1\)
\(=5\sqrt{5}-1\)
a) =8 phần 27 ×( 7 phần 4 - 3 phần 8 + 1 phần 2)
= 8 phần 27 × ( 14 phần 8 - 3 phần 8 + 4 phần 8)
= 8 phần 27 × 15 phần 8
= 5 phần 9
b) = 5 phần 18 × ( 2 phần 5 - 1 phần 3 + 5 phần 6)
= 5 phần 18 × ( 12 phần 30 - 10 phần 30 + 25 phần 30)
= 5 phần 18 × 27 phần 30
= 5 phần 18 × 9 phần 10
= 1 phần 4
c) =( 29 phần 10 - 3 phần 10 + 1 phần 3) ÷ 8 phần 15
=( 87 phần 30 - 9 phần 10 + 10 phần 30) ÷ 8 phần 15
= 88 phần 30 × 15 phần 8
= 44 phần 15 × 15 phần 8
= 44 phần 8
= 11 phần 2
d) = 238 ÷ ( 1 phần 2 + 7 phần 4 - 1 phần 4)
= 238 ÷ ( 2 phần 4 + 7 phần 4 - 1 phần 4)
= 238 ÷ 8 phần 4
= 238 × 4 phần 8
= 238 × 1 phần 2
= 119
Bài 1:
a; (\(\dfrac{1}{4}\)\(x\) - \(\dfrac{1}{8}\)) x \(\dfrac{3}{4}\) = \(\dfrac{1}{4}\)
\(\dfrac{1}{4}x\) - \(\dfrac{1}{8}\) = \(\dfrac{1}{4}\) : \(\dfrac{3}{4}\)
\(\dfrac{1}{4}\)\(x\) - \(\dfrac{1}{8}\) = \(\dfrac{1}{4}\) x \(\dfrac{4}{3}\)
\(\dfrac{1}{4}x\) - \(\dfrac{1}{8}\) = \(\dfrac{1}{3}\)
\(\dfrac{1}{4}x\) = \(\dfrac{1}{3}\) + \(\dfrac{1}{8}\)
\(\dfrac{1}{4}\) \(x\)= \(\dfrac{8}{24}\) + \(\dfrac{11}{24}\)
\(\dfrac{1}{4}x=\dfrac{11}{24}\)
\(x=\dfrac{11}{24}:\dfrac{1}{4}\)
\(x=\dfrac{11}{24}\times4\)
\(x=\dfrac{11}{6}\)
b; \(\dfrac{12}{5}:x\) = \(\dfrac{14}{3}\) x \(\dfrac{4}{7}\)
\(\dfrac{12}{5}\) : \(x\) = \(\dfrac{8}{3}\)
\(x\) = \(\dfrac{12}{5}\) : \(\dfrac{8}{3}\)
\(x\) = \(\dfrac{12}{5}\) x \(\dfrac{3}{8}\)
\(x\) = \(\dfrac{9}{10}\)
a: \(3^2+10:2=9+5=14\)
b: \(13\cdot\left(23+17\right)-17\cdot\left(23+13\right)\)
\(=13\cdot23+13\cdot17-17\cdot23-17\cdot13\)
\(=13\cdot23-17\cdot23\)
\(=-4\cdot23=-92\)
c: \(-8+2\left(x-4\right)=2^3\cdot3^2\)
=>\(2\left(x-4\right)-8=8\cdot9=72\)
=>2(x-4)=72+8=80
=>x-4=40
=>x=44
a)2.(50+35):(-20+3)
=(2.50+35.2):(-20+3)
=(100+70):(-17)
=170:(-17)
=-10
b)(-4).17+(-4).83-(-50)
=(-4).(17+83)-(-50)
=(-4).100-(-50)
=-400-(-50)
=-350
c)10.(-8)+(-10).(-8)
=(-80)+80
=0